Molecular mechanisms of myocardial damage in the hypertensive rats and hypertensive rats with metabolic disorders (diabetes mellitus, atherosclerosis) - Belenichev, I. F.; Abramov, A. V.; Puzyrenko, A.; Bukhtiyarova, N. V.; Gorchakova, N. O.; Bak, P. G.; Бєленічев, Ігор Федорович; Абрамов, Андрій Володимирович; Бухтіярова, Ніна Вікторівна; Бак, Павло Геннадійович (My University, 2022)
Introduction: Despite the success which was achieved in the treatment of arterial hypertension, for optimization of the treatment, it is necessary to study the pathogenesis of primary arterial hypertension and target organ damage on the molecular level. Materials and methods: Our team studied the molecular mechanisms of myocardial damage during arterial hypertension and metabolic disorders. We used the spontaneously hypertensive rats (SHR) as an experimental model, and, additionally, we modeled diabetes mellitus and atherosclerosis in these rats. Results and discussion: Our study obtained evidence of a much higher level of the energy imbalance in the cardiomyocytes and more intensive production of reactive oxygen species in the SHRs with diabetes mellitus and atherosclerosis compared with the healthy animals and the animals with only hypertension. The indicated defections create an environment for further cellular damage – mitochondrial dysfunction, depletion in the thiol-disulfide system, and formation of highly reactive NO products. At the same time, we have noticed a higher activity of the Hsp70 in the hypertensive groups compared with the normotensive animals. The source of these deviations is in the formation of mitochondrial dysfunction of cardiocytes, the cause of which is oxidative modification of the protein structures of mitochondria under conditions of activation of oxidative stress reactions, insufficiency of mPT pores, and impaired mitochondrial chaperone function.
I. F. Belenichev - ORCID ID http://orcid.org/0000- 0003-1273-5314; A. V. Abramov - ORCID ID http://orcid.org/0000-0001-8520-2258; N. V. Bukhtiyarova - ORCID ID http://orcid.org/0000-0003-3499-3111; P. G. Bak - ORCID ID http://orcid.org/0000-0001-9165-4939.
Keywords: arterial hypertension; diabetes mellitus; atherosclerosis; organ damage